1998
DOI: 10.1136/hrt.79.2.191
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction in young people with normal coronary arteries

Abstract: Myocardial infarction occurring in young people with angiographically normal coronary arteries is well described but the pathophysiology of this condition remains unknown. Coronary artery spasm in association with thrombus formation and minimal atheromatous disease or spontaneous coronary artery dissection are possible causes. Two young men presented with severe chest pain after acute alcohol intoxication and each sustained an extensive anterior myocardial infarction. Investigations including intravascular ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
86
0
11

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 42 publications
0
86
0
11
Order By: Relevance
“…7,8,11,12 Theories for the etiology of AMI in young patients with normal coronary arteries include coronary artery spasm, and cocaine-and/or cigarette-smokinginduced vasoconstriction and platelet activation. 19 As would be expected, young AMI patients with normal coronary arteries have been found to have fewer cardiac risk factors than other young AMI patients. 7,8,11,12 The effect of this group of young AMI patients with normal coronary arteries on the evaluation of acute chest pain in patients <40 years old is unknown.…”
Section: Discussionmentioning
confidence: 63%
“…7,8,11,12 Theories for the etiology of AMI in young patients with normal coronary arteries include coronary artery spasm, and cocaine-and/or cigarette-smokinginduced vasoconstriction and platelet activation. 19 As would be expected, young AMI patients with normal coronary arteries have been found to have fewer cardiac risk factors than other young AMI patients. 7,8,11,12 The effect of this group of young AMI patients with normal coronary arteries on the evaluation of acute chest pain in patients <40 years old is unknown.…”
Section: Discussionmentioning
confidence: 63%
“…[1][2][3][4] However, novel functional polymorphisms in hemostasis/inflammation genes remain good candidates for a role in the pathogenesis of MI, 5 especially in younger patients in whom angiographically normal coronary arteries are more frequent and a positive family history of premature coronary disease is more prevalent than in older patients. 6,7 Inflammatory processes are a common underlying mechanism leading to coronary heart disease. Antiinflammatory mechanisms may, therefore, constitute an important protection against MI.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both smoking and alcohol have also been shown to provoke coronary artery spasm. 25,26) Some recent reports have shown that most younger AMI patients were heavy smokers. 5,6) In the current report, all patients were young male smokers and 3 of 5 patients suffered an AMI after drinking alcohol.…”
Section: Discussionmentioning
confidence: 99%